TEACHERS’ PERCEPTION TOWARDS THE USE OF VIRTUAL SCIENCE LAB APPS MODULE IN SECONDARY SCHOOLS - Vineeta, Kumari; Surana, Ajay (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The study aimed to examine the perceptions of secondary school science teachers regarding the usefulness of virtual science lab Apps module in teaching science at the secondary level. The research targeted all secondary school science teachers from Bhagalpur district of Bihar, with a sample of 150 secondary school science teachers. A descriptive survey research design with a quantitative approach utilizing a five-point Likert scale perception tool to investigate the perceptions of secondary school science teachers regarding the usefulness of virtual science lab Apps module in science education was adopted. Data were analyzed using descriptive statistics and Chi-square test. The findings indicate that teachers generally hold positive perceptions of the VSLA module across various demographic and professional variables recognizing their potential to enhance student engagement and improve learning outcomes. The study suggests the need for capacity-building programs and infrastructural support to promote the integration of virtual labs in science education.